2018
DOI: 10.1016/j.jacl.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-linked immunosorbent assay for measuring GPIHBP1 levels in human plasma or serum

Abstract: BACKGROUND GPIHBP1, a glycosylphosphatidylinositol (GPI)-anchored protein of capillary endothelial cells, transports lipoprotein lipase to the capillary lumen and is essential for the lipolytic processing of triglyceride-rich lipoproteins. OBJECTIVE Because some GPI-anchored proteins have been detected in plasma, we tested whether GPIHBP1 is present in human blood, and whether GPIHBP1 deficiency or a history of cardiovascular disease affected GPIHBP1 circulating levels. METHODS We developed two monoclonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Having shown that the "hotspot residues" in the 5D2 epitope participate directly in the binding interface of LPL homodimers, we next investigated the impact of 5D2 on homodimer formation. For these studies, we generated Fab fragments of both mAb 5D2 (37,40) and the human GPIHBP1-specific mAbs RF4 and RE3 (41,42). The epitope for RF4 is centered on Arg 53 −Leu 54 downstream from GPIHBP1's disordered acidic domain (43), whereas RE3 binds GPIHBP1's Ly6/uPAR domain and prevents GPIHBP1 from binding LPL (41).…”
Section: Resultsmentioning
confidence: 99%
“…Having shown that the "hotspot residues" in the 5D2 epitope participate directly in the binding interface of LPL homodimers, we next investigated the impact of 5D2 on homodimer formation. For these studies, we generated Fab fragments of both mAb 5D2 (37,40) and the human GPIHBP1-specific mAbs RF4 and RE3 (41,42). The epitope for RF4 is centered on Arg 53 −Leu 54 downstream from GPIHBP1's disordered acidic domain (43), whereas RE3 binds GPIHBP1's Ly6/uPAR domain and prevents GPIHBP1 from binding LPL (41).…”
Section: Resultsmentioning
confidence: 99%
“…While we had no difficulty in documenting multiple cases of GPIHBP1 autoantibodies with our ELISA [9, 12], we have yet to identify a single case of LPL autoantibodies (even in samples that were thought to have LPL autoantibodies). In the past, the antigens and antibodies used to detect LPL autoantibodies have not been optimal and have resulted in misleading results [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma triglyceride levels were determined with enzymatic assay (Quick Neo TG II, Shino-Test Corporation, Tokyo). Plasma GPIHBP1 levels were measured with a solid-phase monoclonal antibody–based sandwich ELISA (Immuno-Biological Laboratories, Fujioka, Japan) [12]. For the GPIHBP1 ELISA, serum and plasma were diluted 10-fold in PBS; 100 μL of the diluted samples were added to wells of the 96-well ELISA plate.…”
Section: Methodsmentioning
confidence: 99%
“…Seventeen of 22 GPIHBP1 autoantibody patients (patients 1-9, 13-15, 17-21) had very low plasma levels of GPIHBP1, as judged by a monoclonal antibody-based ELISA (35,38,55).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Monoclonal antibody-based ELISAs to measure plasma GPIHBP1 levels have been described in detail (35,38,55), and an ELISA kit to measure GPIHBP1 is available from Immuno-Biological Laboratories. Measuring GPIHBP1 levels is not essential.…”
Section: Downloaded Frommentioning
confidence: 99%